Environmental rights : the development of standards / edited by Stephen J. Turner, Dinah L. Shelton, Jona Razzaque, Owen McIntyre, James R. May. - Turner, Stephen J. (Stephen James); Shelton, Dinah; Razzaque, Jona; McIntyre, Owen; May, James R. (Cambridge University Press, 2019)
Environmental rights, also known as the human rights or constitutional rights that are used for the protection of the environment, have proliferated over the last forty-five years. However, the precise levels of protection that they represent has since been a major question associated with this phenomenon. Environmental Rights: The Development of Standards systematically investigates this question by analyzing the emerging standards of environmental protection that are associated with such rights and the way that those associations are becoming formalized. It covers all of the relevant human rights treaties to illustrate how environmental rights standards are emerging in this dynamic area. Bringing together an elite group of scholars, this book discusses significant new insights into the way that environmental rights are developing, the standards of protection that they confer, and the way that standards in the field of environmental rights can potentially be further developed in the future.